219k views
0 votes
What value of t makes the statement true? (4x3 + 5)(2x3 + 3) = 8x6 + tx3 + 15

User Ogee
by
6.1k points

2 Answers

4 votes

Answer:

The Answer is in fact 22, Just did it on edge

Explanation:

User Moink
by
6.6k points
0 votes

Answer:

t= 22 makes the equation true

Explanation:


(4x^3 + 5)(2x^3 + 3) = 8x^6 + tx^3 + 15

First we remove the parenthesis

We apply FOIL method to multiply it


(4x^3+5)(2x^3+3) \ becomes \ 8x^6 + 22 x^3 + 15

Now we compare the exponents on both sides


8x^6 + 22 x^3 + 15 = 8x^6 + tx^3 + 15

Both sides we have 22x^3 and tx^3

So we set it equal


22x^3 = tx^3

Hence, t = 22

t= 22 makes the equation true

User Jeutnarg
by
6.4k points